2020
DOI: 10.1080/23311886.2020.1740519
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning interaction in South Africa’s higher education: Some weak links

Abstract: The quest to get many people into higher education often crowds out the need for quality teaching and learning achievement if not backed up by resources. Narratives of recurrent concerns in the higher education sector include maintaining access to and quality of higher education, achieving a better outcome and reduce the number of students dropping out of institution. Although successes have been achieved in terms of student access to higher education, the same cannot be said of success rate. What is the weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Furthermore, Tewari and Ilesanmi (2020) concluded that the percentage of academics with PhDs does not only have a significant influence on the research output but also on the quality of such output. In the case of most faculty members in accounting, they do not study beyond CA, while some do master's degrees in their late 40s and a very small number do doctoral work.…”
Section: Iv)mentioning
confidence: 99%
“…Furthermore, Tewari and Ilesanmi (2020) concluded that the percentage of academics with PhDs does not only have a significant influence on the research output but also on the quality of such output. In the case of most faculty members in accounting, they do not study beyond CA, while some do master's degrees in their late 40s and a very small number do doctoral work.…”
Section: Iv)mentioning
confidence: 99%
“…Later, the teacher writes notes for learners to copy and read for the eminent examination. Teachers in South Africa continue to use CT, like what their lecturers used to teach them (Tewari & Ilesanmi, 2020). They claim that this method helps the teachers to cover the pacesetter or schemes of work (Hendripides & Hikmah, 2018), and they continue CT strategies.…”
Section: Related Researchmentioning
confidence: 99%
“…The level of technological awareness amongst students can thus inhibit or aid educational encounters (Zimba et al 2020). Tewari and Ilesanmi (2020) argued that prior to COVID-19, some of these students at higher institutions lacked adequate coping strategies and the ability to adapt within the university system because of low level of preparedness, unavailability of local resources or inputs and student support services amongst other factors. If, for instance, some of these students are not knowledgeable about how these platforms work, it is the sole responsibility of their institutions to provide userfriendly guidelines and tutorials through their LMSs to equip these students for active and engaging teaching and learning experiences (Moonsamy & Govender 2018;Motala & Menon 2020;Mpungose 2020a).…”
Section: E-learning In the South African Educational Landscapementioning
confidence: 99%